ALTERATIONS IN NANOMAGNET ENTRANCES INDUCED BY FIELD AND TEMPERATURE (International Journal of Food and Nutritional Sciences, 2022)
The paper investigates how magnetic entropy varies in nanostructures used for magnetic cooling when the temperature remains constant using model computations. The magnetic entropy is calculated using the mean-field approach, which takes temperature, magnetic field, particle size, anisotropy, and contact strength into account. We consider both isotropic (Heisenberg) and uniaxial anisotropies (Ising and XY). The anisotropy of nanoparticles has a significant impact on their entropy. The energy of anisotropy in atomic ferromagnetism, on the other hand, is substantially smaller than the energy of contact. Isotropic particles, easy-plane particles having a field in the plane, and particles with mild easy axis anisotropy are some of the particles that show the most promise. Nanoparticles should not be larger than 1 nm in size since their relative magnetic direction changes little and has little effect on the entropy change.The researchers utilized model calculations to investigate how magnetic entropy varies in nanostructures used for magnetic cooling when the temperature remains constant. The magnetic entropy is calculated using the mean-field approach, which takes temperature, magnetic field, particle size, anisotropy, and interaction power into account. We consider both isotropic (Heisenberg) and uniaxial anisotropies (Ising and XY). The anisotropy of nanoparticles has a significant impact on their entropy. In contrast, in atomic ferromagnetism, the energy from anisotropy is substantially lower than the energy from interactions. The most promising particles include isotropic particles, easy-plane particles with a magnetic field that stays in the plane, and particles with mild easy axis anisotropy. Nanoparticles should not be larger than 1 nm in size since their relative magnetic direction changes little and has little effect on the entropy change.